2015
DOI: 10.1111/papt.12061
|View full text |Cite
|
Sign up to set email alerts
|

Client experiences of motivational interviewing: An interpersonal process recall study

Abstract: Objectives. To explore clients' experience of the therapy process in Motivational Interviewing (MI) for alcohol abuse. Design.A qualitative study using Grounded Theory. Methods.Interviews with nine clients were conducted using Interpersonal Process Recall (IPR), a methodology which utlises a video recording as a cue to aid memory recall. Clients watched a videotape of their MI session and were asked to identify and describe important moments in the therapy session. The transcribed interviews were then analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
3
19
0
Order By: Relevance
“…Overall, the present results suggest that ambivalence and resistance should not be conceptualized as pejorative patient characteristics or behaviors (Westra, ), but rather a result of the relationship between the therapist and patient that has complex inputs from the patient's pathology, the patient's nondiagnostic characteristics, the dyadic climate, the treatment, the given moment, and so forth. On this point, our results are strikingly similar to Jones and colleagues’ () examination of patient experiences of MI for alcohol abuse. Also using IPR, these investigators reported: “A single session of MI is seen by the clients…as a complex interpersonal interaction between client and therapist, which impacts on the client's cognitive and affective intrapersonal processes” (p. 97).…”
Section: Clinical Practices and Summarysupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the present results suggest that ambivalence and resistance should not be conceptualized as pejorative patient characteristics or behaviors (Westra, ), but rather a result of the relationship between the therapist and patient that has complex inputs from the patient's pathology, the patient's nondiagnostic characteristics, the dyadic climate, the treatment, the given moment, and so forth. On this point, our results are strikingly similar to Jones and colleagues’ () examination of patient experiences of MI for alcohol abuse. Also using IPR, these investigators reported: “A single session of MI is seen by the clients…as a complex interpersonal interaction between client and therapist, which impacts on the client's cognitive and affective intrapersonal processes” (p. 97).…”
Section: Clinical Practices and Summarysupporting
confidence: 90%
“…Thus, it also seems important to gather information directly from the patient when they are in the therapy process. To do so, some researchers have used the interpersonal process recall (IPR) method, a video‐assisted interview to access conscious yet unspoken patient experiences while engaged in professional services (Elliott, ; Jones, Latchford, & Tober, ).…”
mentioning
confidence: 99%
“…The therapists' response to intra-and interpersonal relational difficulties are twofold: first in the moment, by scaffolding relational tasks; and, second, by Interpersonal Process Recall (IPR). Researchers have used the IPR method, as a video-assisted interview to access conscious yet unspoken patient experiences while engaged in professional services (Jones et al 2016). Here, IPR was developed to support therapeutic tasks to deepen experiential processing of self and other within EFGT for clients with ASD.…”
Section: Using Efgt-as To Develop Cognitive-affective Empathy Skillsmentioning
confidence: 99%
“…In terms of counsellor skills, the most helpful elements appear to be a therapist who listens and shows understanding (Glass & Arnkoff, 2000;Duncan & Miller, 2000;Clarke, Rees & Hardy, 2004;Fitzpatrick, Janzen, Chamodraka, Gamberg & Blake, 2009;Gostas, Wiberg, Neander & Kjekkin, 2012;Jones, Latchford & Tober, 2016). From the available evidence being listened to conveys the idea that the therapist is paying attention to the client, reinforcing to the client that they are being heard.…”
Section: Counsellor Characteristics and Skillsmentioning
confidence: 99%